Study, Build and Analyze CAN 2.0 Network Model Using MATLAB: دراسة وبناء وتحليل نموذج لشبكة اتصال تعمل وفق بروتوكول CAN 2.0 باستخدام الماتلاب - RANEEM MAHMOUD MEREI AL-HALABI, IBRAHIM OMAR AL-SHAMI, (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2019)
This research shows designing a model that simulates the performance of CAN 2.0 Protocol (Controller Area Network Protocol) in a seven-node network and a data bus. This model is designed using MATLAB and SimEvents library in Simulink, library (SimEvents) which provides a simulation environment for intermittent events that enables modeling and simulation of any event-based system. This model included simulation of the transmission algorithm used by CAN Protocol, so that data frames are fully integrated and generated on time for some nodes and depending on a given event (whatever) for each other. Thus, all types of messages sent over the real-world network are included. This study presents the building of software model of the network, and the application of several vales of BitRates on the network, and then taking the statistical results and analysis compared to reference values. After drawing diagrams between the priority level of the sent node and the delay time of the message- depending on the values taken from the results of the study-we note that the delay times are significantly increased when the BitRate decreases on the one hand and the priority score decreases on the other hand, which is similar to the real-world network and reference values of the protocol.
Keywords: أولوية العقدة; زمن التأخير; معدل البت; مسار(ناقل); مكتبة SimEvents; بروتوكول CAN